GAMBARAN KARIES GIGI MOLAR PERTAMA PERMANEN DAN STATUS GIZI DI SD KATOLIK 06 MANADO - Manoy, Nadhira Thereza; Kawengian, Shirley E. S.; Mintjelungan, Christy N. (Universitas Sam Ratulangi, 2015)
Abstract: Caries in permanent first molars become the main cause of the high prevalence of revocation due to the first molars are the first tooth eruption so that the child's behavior in maintaining dental health is still lacking, as well as the anatomical shape of the first molar tooth that has a pit and fissure which became a haven leftovers. Nutritional status is one of the factors that influence the occurrence of dental caries. The aim of this study was to determine the status of permanent first molar dental caries and nutritional status of children aged 9-12 years in Manado 6th Catholic elementary school Manado. The method used in this study is an observational descriptive. The study population was all students aged 9-12 years who sit in class IV-VI in Manado 6th Catholic elementary school with the total population 46 students. Sample taken by total population method.The results showed the largest percentage of children with caries of permanent first molars are in children aged 9, 10, and 11 with the percentage of fat nutritional status categories respectively 100%, 83.3%, and 75%. While there is the smallest percentage of children ages 9,10, and 11 normal nutritional status category with a percentage of 33.3% respectively.Keywords: Caries on first permanent molar, nutritional statusAbstrak: Karies pada gigi molar pertama permanen menjadi penyebab utama tingginya prevalensi pencabutan disebabkan karena gigi molar pertama adalah gigi yang pertama erupsi sehingga perilaku anak dalam memelihara kesehatan gigi masih kurang, serta bentuk anatomis dari gigi molar pertama yang memiliki pit dan fissure yang menjadi tempat singgah sisa makanan. Status gizi merupakan salah satu faktor yang memengaruhi proses terjadinya karies gigi. Tujuan penelitian ini adalah untuk mengetahui status karies gigi molar pertama permanen dan status gizi anak usia 9-12 tahun di SD Katolik 06 Manado. Metode penelitian yang digunakan pada penelitian ini adalah deskriptif observasional. Populasi penelitian ini adalah seluruh siswa-siswi usia 9-12 tahun yang duduk di kelas IV-VI di SD Katolik 06 Manado dengan jumlah 46 siswa. Besar sampel penelitian diambil berdasarkan dengan metode total populasi. Hasil penelitian menunjukkan presentase terbesar anak dengan karies molar pertama permanen terdapat pada anak usia 9, 10, dan 11 dengan kategori status gizi gemuk presentase masing-masing 100%, 83,3%, dan 75%. Sedangkan presentase terkecil ada pada anak usia 9,10, dan 11 kategori status gizi normal dengan presentase masing-masing 33,3%.Kata kunci: Karies gigi molar pertama permanen, status gizi